The Effect of Accreditation on Teacher Motivation and Performance in Digital Learning - Jundu Muhammad Mufakkirul Islami; Raden Bambang Sumarsono; Dyan Putri Aprilia; Muazar Habibi (Mudir: Jurnal Manajemen Pendidikan, 2025)
This study aims to examine the influence of accreditation on teacher motivation and performance in the context of digital learning. Accreditation, as an instrument of quality assurance of education, not only functions in assessing the quality of institutions, but also plays a strategic role in increasing the intrinsic motivation and professionalism of teachers. The method used was explanatory research with the Partial Least Square-Structural Equation Modeling (PLS-SEM) approach to 46 junior and senior high school teachers under the auspices of the Lenterahati Islamic Boarding School Foundation. The results showed that accreditation had a significant effect on teacher motivation (R² = 0.520) and teacher performance (R² = 0.598). The validity and reliability of the research instruments have been proven to be strong, supported by composite reliability and AVE values that meet the standards. Hypothesis testing showed that accreditation had a significant positive influence on teacher motivation and performance with a p-value of 0.000. These findings confirm that accreditation is able to create a positive organizational climate, clarify work expectations, and improve teachers' skills in the use of digital technology. However, the study also found that there are other external factors, such as leadership and work climate, that also affect teacher motivation and performance. This study recommends the importance of optimizing technology-based accreditation processes and strengthening professional training programs to support digital transformation in the education sector. Follow-up studies with a wider sample coverage are suggested to enrich understanding of the dynamics of accreditation and teacher capacity building in the digital age.